Optimización y ampliación del sistema de alcantarillado para la Parroquia de San Simón, Cantón Guaranda, Provincia de Bolivar - Rodríguez Elizalde, César Iván (2012)
It presents two design alternatives for the sewage system: the first one consists in the design of the sanitary sewer system with the use of concrete pipes, adding to this the design of the primary treatment plants (imhoff tanks) in the unloading areas ; the second consists of the design of the storm sewer system with the combination of concrete pipes for diameters less than 500 mm and plastic pipe for higher diameters, for which the specifications given by the Ecuadorian Construction Code for works of Sanitation to rural populations, and the design standards of the Metropolitan Public Sanitation and Potable Water Company of Quito.